Ekoteologi Gus Dur: Membaca Kepedulian Lingkungan dari Perspektif Islam Humanis - M. Anzaikhan; Fitri Idani; Amiruddin Amiruddin (Raudhatun Najah Publisher, 2023)
This study aims to explore and analyze Gus Dur’s perspective on the relationship between humans and nature within the framework of humanistic Islamic ecotheology. Using a qualitative approach with a library research method, this study examines Gus Dur’s works such as Islamku, Islam Anda, Islam Kita and Pribumisasi Islam, as well as supporting literature on environmental theology and humanistic ethics. The analysis was conducted using content analysis techniques and a contextual hermeneutic approach to uncover the spiritual, moral, and social values embedded in Gus Dur’s ideas. The findings reveal that Gus Dur’s ecotheological thought emphasizes three main pillars: the consciousness of tawhid that positions nature as a sign of God’s greatness, the human responsibility of khalifah toward environmental preservation, and the principle of universal humanity based on compassion (rahmah).